Beyond Farā’iḍ Texts: Maqāṣid al-Sharīʿah and Substantive Justice in the Banjar Tradition of Equal Inheritance - Maimanah, Maimanah; Nor'ainah, Nor'ainah; Faridah, Siti; Arni, Arni (El-Qist: Journal of Islamic Economics and Business (JIEB), 2026)
Background and objective: This study critically examines the Banjar tradition of equal inheritance distribution as a model of substantive justice that challenges the dominance of farā’iḍ -based formalism in Islamic inheritance law. Although classical jurisprudence prescribes fixed proportional shares, contemporary Islamic legal scholarship has yet to fully theorize how maqāṣid al-sharīʿah can operate not merely as a supplementary interpretive tool, but as an autonomous normative framework capable of reconfiguring inheritance principles toward substantive justice. Methodology: This research adopts a normative juridical approach grounded in systematic textual and conceptual analysis of the Qur’an, hadith, and classical as well as contemporary works of uṣūl al-fiqh, with particular emphasis on maqāṣid al-sharīʿah theory as developed by scholars such as al-Shāṭibī and its modern reinterpretations. Findings: The analysis demonstrates that equal inheritance distribution can be justified within a maqāṣid-oriented framework that prioritizes justice (ʿadl), welfare (maṣlaḥah), and the protection of lineage and wealth (ḥifẓ al-nasl and ḥifẓ al-māl). By reinterpreting inheritance norms through the hierarchy of legal objectives, the study argues that classical proportional rules should be understood as context-bound applications rather than immutable prescriptions, thereby opening space for alternative distributive models that better reflect contemporary socio-economic realities. Contribution: This study contributes to Islamic legal theory by advancing a paradigmatic shift from rule-centered formalism to objective-oriented reasoning, positioning maqāṣid al-sharīʿah as a central epistemological foundation for reconstructing inheritance law and legitimizing substantively just outcomes beyond rigid textualism in modern plural legal contexts.